Kolaborasi Guru dan Orang Tua Tunggal dalam Membina Akhlak Siswa: Studi Kasus di SDN 106153 Klambir Lima - Raudhah; Bahtiar Siregar (Medan Resource Center, 2026)
This study employs a qualitative research design to examine the collaboration between teachers and single parents in shaping students’ moral character at SD Negeri 106153 Klambir Lima, Deli Serdang. The objective of this study is to analyze the forms, processes, and outcomes of teacher–single parent collaboration in supporting students’ moral development. Students from single-parent families often face challenges related to limited parental time and dual-role responsibilities, making school–family collaboration crucial. Data were collected through observations, in-depth interviews, and document analysis involving the principal, teachers, and single parents. The findings reveal the emergence of a structured collaborative model consisting of (1) formal communication mechanisms (parent–teacher meetings, official letters), (2) continuous monitoring tools (prayer control books, communication books, and character report cards), and (3) school-based moral reinforcement strategies (slogans, posters, and habituation practices). This model reflects a synergistic partnership that integrates institutional support and parental involvement. Additionally, quantitative support data indicate strong perceived importance of collaboration, with 69.57% of teachers and 85.71% of parents rating it as very important. These findings imply that implementing a structured and sustainable collaboration model can significantly enhance students’ moral character development, particularly in single-parent family contexts, and may serve as a practical framework for similar elementary education settings.